Export Market Selection : Finnish Producers of Plant-based Meat and Dairy Alternatives - Kuuslampi, Valma (My University, 2021)
The popularity of plant-based food alternatives has grown globally in the past years. Finnish companies have seen a growth opportunity in the increasing demand for plant-based alternatives for meat and dairy products and the companies have started to export plant-based alternatives to foreign markets. Selecting the most optimal export markets is crucial for the companies exporting plant-based alternatives because the conditions of doing business and potential profits vary between different markets. Consequently, export market selection has a direct impact to the companies’ export success. This study aims at understanding how Finnish companies select export markets for plant-based alternatives. Export market selection is approached by analyzing market-level factors and firm-level factors influencing export market selection and the relationships between the different factors. The empirical research was conducted as a qualitative expert interview research. The data was collected by interviewing six Finnish companies which exported plant-based alternatives for meat or dairy products. The empirical findings support the existing theory on factors influencing export market selection on large extent. Finnish companies selected export markets for plant-based alternatives based on the strategic objectives of exports. The companies were found to prefer proximal markets because exporting plant-based alternatives to distant markets was more expensive and complicated. Moreover, the empirical findings revealed partners and networks in foreign markets to have a great influence in export market selection. The findings of the study show export market selection of plant-based alternatives being influenced by the characteristics of the food industry. Furthermore, the emphasis of different factors in export market selection was found to be depended on export market selection process and on the characteristics of the exported product and the home market. The generalizability of the study is limited and therefore further research is required to confirm the findings of this study in other contexts. Further research is also needed to fully understand the influence of the industry and the home market in export market selection.

Kasvipohjaisten ruokavaihtoehtojen suosio on kasvanut viime vuosien aikana maailmanlaajuisesti. Suomalaiset yritykset ovat havainneet kasvumahdollisuuden lihalle ja maitotuotteille vaihtoehtoisten kasvipohjaisten tuotteiden kasvavassa kysynnässä ja yritykset ovat alkaneet viedä kasvipohjaisia vaihtoehtoja ulkomaille. Optimaalisimman vientimarkkinan valinta on tärkeää kasvipohjaisia vaihtoehtoja vieville yrityksille, koska liiketoiminnan edellytykset ja mahdolliset voitot vaihtelevat eri markkinoiden välillä. Vientimarkkinoiden valinnalla on näin ollen suora vaikutus yritysten vientimenestykseen. Tämän tutkimuksen tarkoituksena on ymmärtää, miten suomalaiset yritykset valitsevat vientimarkkinoita kasvipohjaisille vaihtoehdoille. Vientimarkkinoiden valintaa lähestytään analysoimalla markkinatason tekijöitä ja yritystason tekijöitä sekä eri tekijöiden välisiä suhteita. Empiirinen tutkimus toteutettiin laadullisilla asiantuntijahaastatteluilla. Aineisto kerättiin haastattelemalla kuutta suomalaista yritystä, jotka veivät ulkomaille kasvipohjaisia vaihtoehtoja joko lihalle tai maitotuotteille. Tutkimuksen tulokset tukevat suurelta osin olemassa olevaa teoriaa vientimarkkinoiden valintaan vaikuttavista tekijöistä. Suomalaiset yritykset valitsivat vientimarkkinat kasvipohjaisille vaihtoehdoille viennin strategisten tavoitteiden perusteella. Tutkimuksessa havaittiin yritysten suosivan lähellä olevia markkinoita, koska kasvipohjaisten vaihtoehtojen vieminen etäisille markkinoille oli kalliimpaa ja monimutkaisempaa. Empiiriset tulokset toivat myös esiin ulkomaisten kumppaneiden ja verkostojen huomattavan merkityksen vientimarkkinoiden valinnassa. Tutkimuksen tulokset osoittavat elintarviketeollisuuden ominaisuuksien vaikuttavan vientimarkkinoiden valintaan kasvipohjaisille vaihtoehdoille. Tutkimuksessa havaittiin lisäksi eri tekijöiden painotuksen vientimarkkinoiden valinnassa olevan riippuvainen vientimarkkinoiden valintaprosessista sekä vientituotteen ja kotimarkkinoiden ominaisuuksista. Tutkimuksen yleistettävyys on rajallinen, minkä takia lisätutkimusta tarvitaan tutkimustulosten vahvistamiseen muissa konteksteissa. Lisätutkimusta tarvitaan myös, jotta toimialan ja kotimarkkinan vaikutusta vientimarkkinoiden valintaan pystytään ymmärtämään paremmin.
Keywords: Export market selection, plant-based food alternatives, distance